Phase-Separated Nanodroplets Formed below the Cloud Point for the Aqueous Solution of Stereo-Controlled Poly(N-isopropylacrylamide) - Ishihara, Hironori (Langmuir : the ACS journal of surfaces and colloids, 2022)
The relationship between dehydration of polymer chains and the nanodroplet formation through the macroscopic liquid-liquid phase separation (LLPS) has been investigated for the aqueous solution of stereocontrolled poly(N-isopropylacrylamide) (PNiPAm) and poly(N-diethylacrylamide) (PNdEAm). The fluorescent probe method reveals that the temperature range of dehydration for PNiPAm chains is much narrower than that for PNdEAm. The sharp dehydration of polymer chains may give rise to the characteristic thermoresponsive behavior of PNiPAm in water. For meso-rich PNiPAms, the dehydration point (Tdh), which is defined as the temperature where the single chains start assembling in the solution, locates far from the cloud point (Tc). That is, the dehydration of the chain occurs antecedently before the system undergoes a macroscopic LLPS. For PNdEAm, however, the dissociation between Tdh and Tc is not found. For the aqueous solution of PNiPAm with 52% of the meso content, the fluorescence correlation spectroscopy has revealed that nano-order droplets (ca. 45 nm of the hydration radius) are stabilized in the intermediate state between Tdh and Tc. The sharp dehydration of PNiPAm chains may enable an acute condensation of polymers in droplets, causing a viscoelastic hindrance in the coalescence of droplets